The Ambivalent Position of Sleep within the Current Work Regime: A Conceptual Discussion - Emir Kurmuş; Çağatay Topal (Journal of Economy Culture and Society)
Sleep is attracting increasing medical and psychological research interest as well as media interest. This study investigates the socio-economic processes behind this growth in interest. It proposes an analytical framework that examines sleep in the relationships among the body, work, and the rhythms of everyday life within the constraints of today’s capitalist work regime. In this framework, the concept of time pressure is significant for understanding practices and approaches to sleep, as well as the structural processes and contradictions of contemporarycapitalism. Having a work life and accelerating one’s social life are the main determinants of time experience. While sleep, which is a very important part of an employee’s life, becomes limited or restricted, it is nevertheless essential for the sake of efficiency and continuing activity in business and daily life. This study investigates the ambivalent position of sleep with reference to Hartmut Rosa’s concept of social acceleration. This ambivalent position is found to be constructed by the trio of acceleration, flexibility, and time pressure, and it is essentially defined by capitalism.